Improving Student Learning Outcomes on Factors Forming National Integration through the Discovery Learning Model for Students of Class XI MIPA 2 SMA Negeri 1 Bola - Marince Sudriana Biliu (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Studi Islam Sunan Doe, 2024)
Pancasila and Citizenship Education is the study of our daily lives, teaching how to be good citizens, citizens who uphold the values of Pancasila which is the basis of the Indonesian state. This study aims to determine whether the application of the Discovery Learning Model can improve student learning outcomes on the material of Factors Forming National Integration in Class XI MIPA 2 SMA Negeri 1 Bola. The approach in this research is qualitative. The research strategy used is Classroom Action Research, where the process of implementing the action is summarised in the action cycle. The research subjects were students of class XI MIPA 2, totalling 20 people. The data collection technique used in this study was a test technique, namely the initial test and the final test. The data analysis technique in this research is percentage. Based on the results of the research conducted, it can be concluded that the use of the Discovery Learning Model can improve student learning outcomes on the material of Factors Forming National Integration of students in class XI MIPA 2 SMA Negeri 1 Bola. This increase is marked by the increase in students' PPKN learning achievement starting from pre-action which reached 30% and increased from cycle to cycle, where the percentage of classical learning completeness in cycle I reached 50%, while classical learning completeness in cycle II increased to 90%.